2013
DOI: 10.1149/2.016303jss
|View full text |Cite
|
Sign up to set email alerts
|

Role of Potassium Permanganate-Based Solutions in Controlling the Galvanic Corrosion at Al-Co Interface

Abstract: Al-Co metal gate has been recently proposed both for 25 and 11 nm devices as an alternative for Al-Ti used for 45 nm structures. The polishing dispersions used for Al-Ti gates when tested on Al-Co showed severe pitting and static etch rates upto ∼10 nm/min. The present work describes the development of the required chemistry to reduce the corrosion potential (E corr ) gap between Al and Co and minimize galvanic corrosion. The effect of pH, several oxidizers and additives on the open circuit potentials (E oc ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…It is found that KMnO 4 is a good oxidizer which can achieve oxidbillity preservation and be used to enable the formation of a protective MnO 2 film to reduce the corrosion potential gap and minimize galvanic corrosion. 8,9 According to the Pourbaix diagram of Al, 7 the oxide or hydroxide is not stable and can be dissolved into the slurry under the acidic environment and the rate constant k 32 :…”
Section: Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…It is found that KMnO 4 is a good oxidizer which can achieve oxidbillity preservation and be used to enable the formation of a protective MnO 2 film to reduce the corrosion potential gap and minimize galvanic corrosion. 8,9 According to the Pourbaix diagram of Al, 7 the oxide or hydroxide is not stable and can be dissolved into the slurry under the acidic environment and the rate constant k 32 :…”
Section: Modelingmentioning
confidence: 99%
“…During the first stage, the excess Al bulk is polished till the remaining thickness is just several hundreds of angstroms, and then the remaining Al, barrier and oxide layers are removed on the second polishing step. Because of the process control of the metal barriers, such as Al-Ti, or Al-Co and SiO 2 at very similar rates after removing the overburden alloy films, 8 the dishing value is mainly coming from the oxide and aluminum removal process. Therefore, the present model just focuses on this process especially after the clear removal of the barrier above oxide.…”
Section: Effect Of Complexing Agent On Mrr-the Simulation Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Відомий також спосіб покриття поверхні порівняно менш благородними металами, які легко піддаються окисненню, утворюючи на поверхні оксидні або гідроксидні захисні шари [6][7][8][9][10]. Однак такі самочинно утворені захисні шари бувають недостатньо однорідними, тому для їхнього ущільнення використовують збагачені на оксиген сполуки [11][12][13][14][15]. За теорією корозії [16] на поверхні сплаву утворюється захисний оксид легуючого елемента, який ускладнює дифузію та окиснення основного металу.…”
unclassified